Electron impact mass spectrometry of some 3-[3-(4-aryl)-1, 2, 4-oxadiazole-5-yl] acyl arylaldehyde hydrazone derivatives. Issue 3 (2000) - Leite Leite, Lúcia Fernanda C. C. Lúcia Fernanda C. C.; Barreiro Barreiro, Eliezer J. Eliezer J.; Ramos Ramos, Mozart N. Mozart N.; Silva Silva, João Bosco P. João Bosco P.; Galdino Galdino, Suely L. Suely L.; Pitta Pitta, Ivan R. Ivan R.
Abstract : This report describes the results of a study of the electron impact mass spectrometry behaviour of 20 new compounds of a series of 3-[3-(4-aryl)-1, 2, 4-oxadiazole-5-yl] acyl arylaldehyde hydrazone derivatives. The most relevant possible fragmentation patterns of this class of compounds under electron impact are outlined.